2001
DOI: 10.1017/s0016672301005341
|View full text |Cite
|
Sign up to set email alerts
|

Two-generation analysis of pollen flow across a landscape. III. Impact of adult population structure

Abstract: The rate and distance of instantaneous pollen flow in a population are parameters of considerable current interest for plant population geneticists and conservation biologists. We have recently developed an estimator (Φft) of differentiation between the inferred pollen clouds that fertilize several females, sampled within a single population. We have shown that there is a simple relation between Φft and the average pollen dispersal distance (δ) for the case of a population with no geographic structure. Though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(139 citation statements)
references
References 36 publications
(54 reference statements)
5
132
0
2
Order By: Relevance
“…On the other hand, the indirect approach (KINDIST) used in this study requires correlation of paternity to be a continuous and significant function of a distance between mother trees (Robledo-Arnuncio et al 2006. Moreover, the latter is assumed to result entirely from pollen dispersal and not population genetic structure (Austerlitz and Smouse 2001). The absence of correlation between genetic and geographic distance found in the Tatras (Dzialuk et al 2014) suggests that the observed pollen structure was indeed a result of limited pollen dispersal.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, the indirect approach (KINDIST) used in this study requires correlation of paternity to be a continuous and significant function of a distance between mother trees (Robledo-Arnuncio et al 2006. Moreover, the latter is assumed to result entirely from pollen dispersal and not population genetic structure (Austerlitz and Smouse 2001). The absence of correlation between genetic and geographic distance found in the Tatras (Dzialuk et al 2014) suggests that the observed pollen structure was indeed a result of limited pollen dispersal.…”
Section: Discussionmentioning
confidence: 92%
“…Using the TWOGENER approach for Coca, we obtain an intraclass correlation of male cpSSR haplotypes within maternal sibships of F ft ¼ 0:280. Using the iterative estimation techniques in Austerlitz and Smouse (2002), we obtain an adjusted value of r 0 ¼ 0.30470.060, within estimation error of the estimate of 0.317 obtained from the categorical assignment of paternity.…”
Section: Indirect Estimationmentioning
confidence: 70%
“…Lacking paternal designation, we have no directly observable measures of r 0 and r gh , but we can extract indirect estimates from the G Â G matrix of pairwise f gh estimates produced by AMOVA (Austerlitz and Smouse, 2002;Austerlitz et al, 2004). Using the TWOGENER approach for Coca, we obtain an intraclass correlation of male cpSSR haplotypes within maternal sibships of F ft ¼ 0:280.…”
Section: Indirect Estimationmentioning
confidence: 99%
“…the probability for two randomly drawn seeds to have been pollinated by the same father), and when associated with an isolation-by-distance model allows for real-time pollen dispersal estimation (Austerlitz and Smouse, 2001). We used POLDISP software to: (i) compute global and pairwise^f t (Austerlitz and Smouse, 2002) for each pair of maternal sibships within each site (Clonee and Kildalkey), (ii) compute^f t per phenological group and for each population: native or plantation and (iii) estimate the pollen dispersal function assuming an isolation-by-distance model. We also computed relative measures of correlated paternity between maternal sibship pairs using the similarity index for the male gametes C(z) separated by a distance z.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of native trees produced seeds, and therefore the sampling design was set up to include a greater number of trees with fewer seeds taken from each individual tree rather than a few large progenies, as recommended for landscape-level studies (Austerlitz and Smouse, 2002;Miyamoto et al, 2008). Thus, eight seeds were sampled per tree for 45 and 47 maternal native trees at the Clonee and Kildalkey sites, respectively ( Figure 1 and Table 1).…”
Section: Samplingmentioning
confidence: 99%